If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3(x + -3) = 9 + 4x + 12 Reorder the terms: 5x + -3(-3 + x) = 9 + 4x + 12 5x + (-3 * -3 + x * -3) = 9 + 4x + 12 5x + (9 + -3x) = 9 + 4x + 12 Reorder the terms: 9 + 5x + -3x = 9 + 4x + 12 Combine like terms: 5x + -3x = 2x 9 + 2x = 9 + 4x + 12 Reorder the terms: 9 + 2x = 9 + 12 + 4x Combine like terms: 9 + 12 = 21 9 + 2x = 21 + 4x Solving 9 + 2x = 21 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 9 + 2x + -4x = 21 + 4x + -4x Combine like terms: 2x + -4x = -2x 9 + -2x = 21 + 4x + -4x Combine like terms: 4x + -4x = 0 9 + -2x = 21 + 0 9 + -2x = 21 Add '-9' to each side of the equation. 9 + -9 + -2x = 21 + -9 Combine like terms: 9 + -9 = 0 0 + -2x = 21 + -9 -2x = 21 + -9 Combine like terms: 21 + -9 = 12 -2x = 12 Divide each side by '-2'. x = -6 Simplifying x = -6
| 6x+6=12+5x | | X-(4-1)=7 | | x+2-3x-16=0 | | 12.6x-3.7x=267 | | 8=5v-3-4v | | 2x^3-9x^2+16x-12=0 | | 30=10q | | 9-7x-x=-79 | | 5n=-8n+n | | 90=37.08+.50x | | 5x+3+2x-6=4+12 | | 2(3x+5)-2x+2=0 | | 24=2x+16 | | 48-3x=7x | | 5(4k-2)=6k-38 | | -2(3x-6)=-24 | | (x-45)+x+x+(x-45)+(x-45)=540 | | 3y-20=.5 | | 48-3x=48-7x | | f/3=4 | | 5=c-12 | | 13y-10y-13=39.74 | | 22+2x=-6(1-x) | | 34-4m=-5m+4(m+7) | | r+32=63 | | 6x-24=89 | | 1.8+0.6=0.6-y+0.6 | | +1m/4=-1 | | 24a^7b^5+8ab^2-64ab^5=0 | | -7(b+6)=-37-8b | | 21x-5=7+18x | | -(5x+3)-4x= |